Contemporary political ideologies movements and regimes - Macridis, Roy C. (Harper Collins College Publisher, 1996)
[This book] features lucid accounts of the political ideas that define the most important political controversies of our time. Professor Mark Hulliung has prepared a timely revision of the late Roy Macridis's leading text. Five chapters are new to this edition. This sixth edition offers a more current analysis of fascism, nationalism, Marxism, anarchism, a historically informed view of multiculturalism and its impact around the world, and a case study of the student movements in the 1960s which shaped the politics of an entire generation now in power. Throughout the text, readers are invited to enlarge their understanding of contemporary political controversies by comparing America to European countries.